Are Microfibers a Threat to Marine Invertebrates? A Sea Urchin Toxicity Assessment - dos Santos, Jennifer Barbosa; Choueri, Rodrigo Brasil; dos Santos, Francisco Eduardo Melo; de Oliveira Santos, Laís Adrielle [UNESP]; da Silva, Letícia Fernanda [UNESP]; Nobre, Caio Rodrigues; Cardoso, Milton Alexandre; de Britto Mari, Renata [UNESP]; Simões, Fábio Ruiz; Delvalls, Tomas Angel; Gusso-Choueri, Paloma Kachel (MDPI, 2024)
The rise of "fast fashion" has driven up the production of low-cost, short-lived clothing, significantly increasing global textile fiber production and, consequently, exacerbating environmental pollution. This study investigated the ecotoxicological effects of different types of anthropogenic microfibers-cotton, polyester, and mixed fibers (50% cotton: 50% polyester)-on marine organisms, specifically sea urchin embryos. All tested fibers exhibited toxicity, with cotton fibers causing notable effects on embryonic development even at environmentally relevant concentrations. The research also simulated a scenario where microfibers were immersed in seawater for 30 days to assess changes in toxicity over time. The results showed that the toxicity of microfibers increased with both concentration and exposure duration, with polyester being the most toxic among the fibers tested. Although synthetic fibers have been the primary focus of previous research, this study highlights that natural fibers like cotton, which are often overlooked, can also be toxic due to the presence of harmful additives. These natural fibers, despite decomposing faster than synthetic ones, can persist in aquatic environments for extended periods. The findings underline the critical need for further research on both natural and synthetic microfibers to understand their environmental impact and potential threats to marine ecosystems and sea urchin populations.